Emotional Scars from COVID-19: The Wave of Post-Traumatic Stress Disorder - Mazzotti, Eva; Costantini, Anna (Advances in Social Sciences Research Journal, 2022)
This study examined the prevalence and the characteristics of post-traumatic stress disorder (PTSD), as measured by IES-R, in a sample of 1464 online respondents 4 or more months after the first pandemic wave in Italy. Results. 375 (25.61%) of respondents were probable case of PTSD. In multivariate logistic regression analysis, the variables independently associated with PTSD were peritraumatic distress (Adjusted Odds Ratio, AOR 25.69; 95% Confidence Interval, CI 17.96-36.74), have been in quarantine (AOR 3.16; 95%CI 1.94-5.15), have been worried about dying (AOR 2.58; 95%CI 1.74-3.83), female gender (AOR 2.49; 95%CI 1.64-3.78), having used sleep remedies (AOR 2.25; 95%CI 1.549-3.29), feeling shunned by others as a possible source of contagion (AOR 1.92; 95%CI 1.33-2.78), and having tested positive for a COVID-19 (as protection factor) (AOR 0.25; 95%CI 0.08-0.80), after adjusting for age. Conclusions. One in four of people could be a case of PTSD and could have important long-term physical and psychological consequences. The COVID-19 pandemic is connoted as a "trauma" that can favor the development of a PTSD, which if not treated in addition to psychological, social and occupational distress, could cause in the long term, biological damage. It is therefore important to recognize the symptoms of PTSD for early diagnosis and timely treatment chosen from those that have also been shown to be effective in promoting neurogenesis.